KIAT GURU PENDIDIKAN JASMANI DALAM MENDIRIKAN BISNIS OLAHRAGA - Komari, Amat (Jurnal Pendidikan Jasmani Indonesia, 2011)
<p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 79.4pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 240.7pt; mso-height-rule: exactly;">Abstract <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">Among the spreading of shopping centers bring <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">amenity for amount of people; not aside from Physical <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">Education teacher who interested for a business. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">Someone’s shopping activity in fulfilling daily need, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">reading news, listening radio, television, transport <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">service and also private vehicle for transportation <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">fluency; all those represent activity of business for <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">the existence of service provider and consumer side. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">Some needs of that human being represented <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">business field to others so that the interaction of <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">various needs will create business fields, not aside <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">from sport business, for example founding sport shop, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">training, organizing a game, or sport activities and <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">also serve the needs of athletes such as clothes, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">food and also calorie-contained beverage. Sport <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">businesses in Indonesia are in partial existed, but <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">such condition still needs the stakeholder touch in <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">order to obtain more maximal result. In National <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">Seminar of Sportsmanship Industry, it have been told <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">some business chances to public that sport-related <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">company, included home industry (e.g. shuttlecock, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">sport t-shirt, medal graver, self-defense uniform, glove <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">softball, event organizer, etc.) which have expanded <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">themselves so that necessary to snuggle up to be <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">Sport Industry. The Law of National Sportsmanship <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">System has given chances for every citizen to plunge <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">in sport business world, not aside from Physical <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">Education teacher. Consider their involvements, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">Physical Education teacher with their activity quite a <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">lot related to sport; of course they understand so much <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">the needs of sport perpetrators which represent <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">potential business field for. In starting or developing <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">sport business, Physical Education teacher needs <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">certain tricks, such as: (1) have strong willingness to <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">try by stocked of never give up spirit as well as learning <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 56.75pt; mso-element-top: 261.65pt; mso-height-rule: exactly;">desire, (2) the run-business is easy reached in ability, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 311.8pt; mso-element-top: 241.0pt; mso-height-rule: exactly;">management, and monetary source, and also that <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 311.8pt; mso-element-top: 241.0pt; mso-height-rule: exactly;">activity have to pleasant, (3) seeing market potency <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 311.8pt; mso-element-top: 241.0pt; mso-height-rule: exactly;">and society needs and also majoring customer <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 311.8pt; mso-element-top: 241.0pt; mso-height-rule: exactly;">satisfaction, (4) in attracting the customer purchasing <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 311.8pt; mso-element-top: 241.0pt; mso-height-rule: exactly;">ability, it’s necessary using cost leadership strategy, <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 311.8pt; mso-element-top: 241.0pt; mso-height-rule: exactly;">and (5) for managed-company survival, it’s using <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 262.7pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 311.8pt; mso-element-top: 241.0pt; mso-height-rule: exactly;">forwards, rear, and horizontal integration strategies. <p class="MsoNormal" style="margin-bottom: .0001pt; line-height: normal; mso-pagination: none; layout-grid-mode: char; mso-layout-grid-align: none; text-autospace: none; mso-element: frame; mso-element-frame-width: 251.2pt; mso-element-wrap: auto; mso-element-anchor-horizontal: column; mso-element-left: 311.8pt; mso-element-top: 344.65pt; mso-height-rule: exactly;">Keywords: Business, Sport, Physical Education.